Borate transporter SLC4A11 mutations cause both Harboyan syndrome and non-syndromic corneal endothelial dystrophy - Julie Désir; Graciela Moya; Orit Reish; Nicole Van Regemorter; H. Deconinck; Karen L. David; Françoise Meire; Marc Abramowicz (2007)
Harboyan syndrome, or corneal dystrophy and perceptive deafness (CDPD), consists of congenital corneal endothelial dystrophy and progressive perceptive deafness, and is transmitted as an autosomal recessive trait. CDPD and autosomal recessive, non-syndromic congenital hereditary endothelial corneal dystrophy (CHED2) both map at overlapping loci at 20p13, and mutations of SLC4A11 were reported recently in CHED2. A genotype study on six families with CDPD and on one family with either CHED or CDPD, from various ethnic backgrounds (in the seventh family, hearing loss could not be assessed because of the proband's young age), is reported here. Novel SLC4A11 mutations were found in all patients. Why some mutations cause hearing loss in addition to corneal dystrophy is presently unclear. These findings extend the implication of the SLC4A11 borate transporter beyond corneal dystrophy to perceptive deafness.